Building Bridges to the Workforce: The Role of Career Decision-Making Self-Efficacy in Vocational Students' Work Readiness - Alita Dwi Nuraini; Dewi Handayani Harahap; Femmy Lekahena (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The open unemployment rate (TPT) of vocational school graduates in February 2025 will reach 8%, the highest compared to other levels of education. In Yogyakarta, the unemployment rate of vocational school graduates in Sleman Regency was recorded at 5.02%. This high unemployment rate reflects a serious challenge in optimizing the role of vocational education as a bridge to the world of work. This study aims to determine the relationship between career decision-making self-efficacy (CDMSE) and work readiness in grade XII students of SMK X. This study uses a quantitative method with a correlational design. The research sample amounted to 152 students who were selected through a population study. Data collection was carried out using the CDMSE scale and the work readiness scale. Data analysis using the Pearson Product Moment correlation test showed a positive and significant relationship between CDMSE and work readiness in grade XII students of SMK X (r = 0.469, p < 0.05). The results of this study show that the higher the CDMSE, the higher the student's job readiness. These findings indicate the importance of strengthening self-efficacy in career decision-making to improve the work readiness of vocational school students.Tingkat pengangguran terbuka (TPT) lulusan SMK pada Februari 2025 mencapai 8%, tertinggi dibandingkan jenjang pendidikan lain. Di Yogyakarta, tingkat pengangguran lulusan SMK di Kabupaten Sleman tercatat sebesar 5,02%. Tingginya angka pengangguran ini mencerminkan tantangan serius dalam mengoptimalkan peran pendidikan vokasi sebagai jembatan menuju dunia kerja. Penelitian ini bertujuan untuk mengetahui hubungan antara career decision-making self-efficacy (CDMSE) dengan work readiness pada siswa kelas XII SMK X. Penelitian ini menggunakan metode kuantitatif dengan desain korelasional. Sampel penelitian berjumlah 152 siswa yang dipilih melalui studi populasi. Pengumpulan data dilakukan menggunakan skala CDMSE dan skala work readiness. Analisis data menggunakan uji korelasi Pearson Product Moment menunjukkan adanya hubungan positif dan signifikan antara CDMSE dengan work readiness pada siswa kelas XII SMK X (r = 0,469, p < 0,05). Hasil penelitian ini menunjukkan bahwa semakin tinggi CDMSE, maka semakin tinggi pula kesiapan kerja siswa. Temuan ini mengindikasikan pentingnya penguatan efikasi diri dalam pengambilan keputusan karir untuk meningkatkan kesiapan kerja siswa SMK.